Long-term Impacts of Global Food Crisis on Production Decisions : Evidence from Farm Investments in Indonesia - Nose, Manabu; Yamauchi, Futoshi (Taylor and Francis, 2016)
This paper estimates farmers’ investment response to food price spikes using household panel data collected before and after the 2007/08 food price crisis in Indonesia. We found that an increase in farmers’ terms-of-trade allowed relatively large crop-producing farmers to increase their investments at both extensive and intensive margins. Food price spikes had a significant income effect among farmers whose production surplus is large for market sales. During the food price crisis, large farmers particularly increased machine investments, which saved some labour inputs, pointing to the importance of complementarities between land and machine investments.